SEJARAH SOSIAL HUKUM ISLAM DI ASIA TENGGARA; STUDI PEMBERLAKUAN DAN PENGKODIFIKASIAN HUKUM ISLAM DI MALAYSIA - Ahmad Fathoni (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2015)
In Southeast Asian countries today, Islamic law issues besides worship and ahwal al-syakhsiyyah field (Family) are a cultural phenomenon of the people which the background can be seen from various aspects. Islamic law in Malaysia has experienced a dynamic and sustainable development, both through the channel of political infrastructure and superstructure. In addition, the dynamics of development is motivated by the realities, demands and support, as well as the will for transformation efforts of Islamic law into the legal system of Malaysia. This paper will attempt to explore the social and political situation of the applicability of Islamic law in Malaysia